Osteonecrosis of the jaw: a rare and devastating side effect of bisphosphonates. Issue 1010 (14th January 2010) - Ryan, P; Saleh, I; Stassen, L F A
Abstract : Evidence has emerged that bisphosphonate use in cancer patients is associated with osteonecrosis of the jaw. This form of osteonecrosis has been termed bisphosphonate induced osteonecrosis of the jaw (BIONJ). BIONJ is commonly precipitated by a tooth extraction in patients treated with long term, potent, high dose intravenous bisphosphonates for the management of myeloma, breast or prostate cancer. The overall prevalence of BIONJ is about 5% in patients with these malignancies. Current evidence shows that the risk of BIONJ in non-cancerous patients, such as those with osteoporosis, is very low and appears to be comparable with that of the general population. Prescribing physicians need to encourage cancer patients to see their dentists before the initiation of bisphosphonate treatment, and regularly thereafter.